2014
DOI: 10.1111/avj.12145
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Merino ewe mortality on the Northern Tablelands of New South Wales, Australia

Abstract: Mortality of Merino ewes can be significantly reduced by management methods that reduce WEC, maintain BW and increase the FS. For Merino ewes on the Northern Tablelands of NSW, improved animal welfare and economic benefits may be achieved by maintaining sheep with WEC < 1200 epg, BW > 35 kg and FS > 2.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…This agrees with New Zealand results in which poor BCS was reported as a common cause of ewe mortality [18]. These results are also consistent with international data in which mortality rates were increased in poor-BCS ewes [6,12]. It is possible that for some of these poor-BCS ewes, the poor BCS is a proxy for other diseases [5,18,19]; therefore, further investigation into the underlying causes of poor BCS in commercial ewes is required.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This agrees with New Zealand results in which poor BCS was reported as a common cause of ewe mortality [18]. These results are also consistent with international data in which mortality rates were increased in poor-BCS ewes [6,12]. It is possible that for some of these poor-BCS ewes, the poor BCS is a proxy for other diseases [5,18,19]; therefore, further investigation into the underlying causes of poor BCS in commercial ewes is required.…”
Section: Discussionsupporting
confidence: 90%
“…Annual dead/missing incidence, considered a proxy for mortality rates, ranged from 3.5 to 20.8% in Years 1-5 (Table 5). This is comparable to previously reported annual on-farm mortality rates of 2.8-27.0% in New Zealand [15,16,18,19], 2.7-22.0% in Australian extensive flocks [11,12,20,33], and 3.0-10.0% for flocks based in the United Kingdom and Ireland [2,[21][22][23]. However, in this study, mortality incidences in Year 6 were between 7.0 and 40.2% (Table 5).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Three studies across a range of Australian sheep production zones and systems have determined annual ewe mortality rates to range from 2.2% to 6% per annum in well managed, relatively disease‐free flocks 3–5 . Mortality rates, however, averaged 6% per annum in merino flocks affected by flystrike, 3 10% in merino ewes affected by haemonchosis 6 and 11% in crossbred flocks due to peri‐parturient problems and heliotrope poisoning 3–5 . Overseas, a large New Zealand survey of Romney Marsh ewes found that mortality rates averaged 2.8% per annum, 7 whereas a smaller survey of hill farms in the United Kingdom found that ewe mortality rates averaged between 3% and 4% per annum 8 …”
mentioning
confidence: 99%